Validasi Penetapan Kadar Kuersetin Ekstrak Etanol Daun Kemangi (Ocimum sanctum L) Secara Kromatografi Cair Kinerja Tinggi (KCKT) - Kurniawati, Evi; Tri Puji Lestari; Esti Ambar Widyaningrum (Media Farmasi, 2024)
Validation of Determination of Quercetin Content of Ethanol Extract of Basil Leaves (Ocimum sanctum L) by High-Performance Liquid Chromatography (HPLC) One of the Indonesian plants that has medicinal properties is the basil plant (Ocimum sanctum L). There are several active substances contained in basil leaves, such as the flavonoid compound quercetin, which is known to be found in basil. Quercetin has several very useful biological activities such as antibacterial, anticancer, antiviral, and anti-inflammatory. Determination of quercetin content in basil leaves requires a valid method. The selection of an analytical method that has good specificity, linearity, accuracy and precision is a very important aspect in order to obtain acceptable results. The aim of this research is to validate the determination of quercetin levels contained in the ethanol extract of basil leaves (Ocimum sanctum L) using high-performance liquid chromatography (HPLC). The HPLC system used is the Shimadzu DGU-20A5R type with a Uv-Vis detector at a wavelength of 374 nm. The stationary phase used was a C18 column with a mobile phase of a mixture of methanol: aqua bi destillate in a ratio of 59:41 which flowed isocratically at a rate of 1.2 mL/minute. Assay validation parameters include selectivity, linearity, precision, and accuracy tests. The research results showed that the quercetin method was validated with all parameters meeting the requirements. The linearity test produces a correlation value (r) = 0.9919, good selectivity, precision produces an RSD of less than 2% and accuracy produces a recovery percentage in the range of 98-102%. The average quercetin content in the ethanol extract of basil leaves is 12.70% w/w. Salah satu tanaman Indonesia yang berkhasiat sebagai obat adalah tumbuhan kemangi (Ocimum sanctum L). Terdapat beberapa kandungan zat aktif dalam daun kemangi seperti senyawa flavanoid kuersetin diketahui terdapat dalam kandungan kemangi. Kuersetin memiliki beberapa aktivitas biologi yang sangat bermanfaat seperti antibakteri, antikanker, antivirus, dan antiinflamasi. Penentuan kadar kuersetin dalam daun kemangi membutuhkan metode yang valid. Pemilihan metode analisis yang memiliki spesifitas, linieritas, akurasi dan presisi yang baik merupakan aspek yang sangat penting agar diperoleh hasil yang dapat diterima. Tujuan dari penelitian ini adalah untuk melakukan validasi penetapan kadar kuersetin yang terkandung dalam ekstrak etanol daun kemangi (Ocimum sanctum L) secara kromatografi cair kinerja tinggi (KCKT). Sistem KCKT yang digunakan adalah tipe Shimadzu DGU-20A5R dengan detektor Uv-Vis pada panjang gelombang 374 nm. Fase diam yang digunakan adalah kolom C18 dengan fase gerak campuran methanol : aqua bidestilata pada perbandingan 59:41 yang dialirkan secara isokratik pada laju 1,2 mL/menit. Parameter validasi metode penetapan kadar kuersetin meliputi uji selektivitas, linieritas, presisi dan akurasi. Hasil penelitian menunjukkan bahwa metode KCKT yang digunakan tervalidasi yang ditunjukkan dengan semua parameter uji memenuhi syarat yang ditetapkan. Uji linieritas menunjukkan nilai korelasi (r) = 0,9919, selektivitas baik, presisi menghasilkan RSD kurang dari 2% dan akurasi menghasilkan persen rekoveri pada kisaran 98-102%. Rata-rata kandungan kuersetin dalam ekstrak etanol daun kemangi adalah 12,70% b/b.